Comparative transcriptome analysis on candidate genes involved in lipid biosynthesis of developing kernels for three walnut cultivars in Xinjiang - Wenqiang Wang; Hao Wen; Qiang Jin; Wenjun Yu; Gen Li; Minyu Wu; Hongjin Bai; Lirong Shen; Cuiyun Wu (Food Science and Human Wellness)
Walnut (Juglans regia L.) is a good source of lipids and polyunsaturated fatty acids (PUFAs). In order to explore the biosynthesis molecular mechanism of oil accumulation and fatty acid (FA) synthesis in walnut, the samples at different development periods of three walnut cultivars, ‘Zhipi’ (ZP), ‘Xinwu 417’ (W417) and ‘Xinwen 81’ (W81) were collected for transcriptomic analysis. The analysis of oil accumulation and FA profiles showed that the oil content in mature walnut kernel was nearly 70 %, and over 90 % of FAs were PUFAs. We identified 126 candidate genes including 64 genes for FA de novo synthesis, 45 genes for triacylglycerol assembly, and 17 genes for oil bodies involved in lipid biosynthesis by RNA-sequencing. Ten key enzymes including ACCase, LACS6, LACS8, SAD, FAD2, FAD3, LPAAT1, DGAT2, PDAT2, and PLC encoded by 19 genes were highly associated with lipid biosynthesis. Quantitative PCR analysis further validated 9 important genes, and the results were well consistent with our transcriptomic data. Finally, 5 important transcription factors including WRI1, ABI3, FUS3, PKL and VAL1 were identified, and their main regulatory genes might contain ACCase, KASⅡ, LACS, FAD3 and LPAAT which were determined through correlation analysis of expression levels for 27 walnut samples. These findings will provide a comprehensive understanding and valuable information on the genetic engineering and molecular breeding in walnut.